Characteristic and flavor profiles of specialty Arabica coffee derived from fermentation with protease, at different conditions - Wongyai Intugon; Suttisintong Khomson; Thumthanaruk Benjawan; Foophow Tita; Yasutomo Tamaki; Rungsardthong Vilai (E3S Web of Conferences)
Coffee is one of the most popular beverages in the world. Development of coffee beans with specific flavor profiles can enhance the quality and value of the product. In this study, the flavor profiles of Arabica coffee (Coffea arabica L.) beans treated with protease, at different enzyme loading, time, and pH, were investigated using gas chromatography tandem mass spectrometry (GC-MS/MS). The coffee beverages were evaluated for their sensory characteristics by Q-Grader (professional coffee taster). The coffee beans obtained from protease hydrolysis exhibited specific and unique volatile compounds or flavor profiles than the control (coffee beans without enzyme loading). Specific volatile profiles in the enzymetreated coffee beans, such as isopropenyl acetate, 2-acetyl-5-methylfuran, and delta-dodecalactone were identified. Coffee beverages obtained from roasted coffee beans from protease fermentation with 0.84% protease, pH 6.2 at 41 h (R-FP5), and 1.00% protease, pH 5.0 at 30 h (R-FP8) were evaluated as specialty coffees (a score of 79.75 points), showing their specific aroma profiles as fruity, spice, mango, dry fruit, ripe fruit, nutty and tamarind notes. The present work revealed that enzymatic fermentation of the green Arabica coffee beans is a promising method for the modulating and improving of specialty coffee with specific acceptable flavors and aromas.